KAJIAN TINGKAT PELAYANAN PERSIMPANGAN UNTUK MENGURANGI TINGKAT KEMACETAN LALU LINTAS DI KOTA SEMARANG - Saputra, Sofiyan Agus (Geo-Image, 2016)
The aim in this research are: 1) Determine the service level of traffic at intersections, 2) Knowing how to solve traffic congestion at the intersection during rush hour. The analysis technique used is the technique of analysis of traffic flow with the formula Q = QLv + QHv + empHv + QMC + empMc analysis techniques degree of saturation with the formula DS = Q / C. Results of the research: 1) The level of service at the junction with road Siliwangi Kalibateng have a service level A, road Abdul Rahman Saleh C, road Yos Sudarso C, road Pamularsih B and road Siliwangi B. The intersection Pedurungan with Jalan Brigjen Sudiarto has a service level A, Jalan Soekarno-Hatta has a service level B, and Jalan Brigjen Sudiarto have service level B. 2) jams that occur at the intersection and the intersection Pedurungan Kalibanteng have a similar problem.